Impact of Sustainable Practices on the Performance of Manufacturing SMEs in India - Sami, Sania; Roychowdhury, Soma (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : Sustainable manufacturing practices (SMP) represent a comprehensive framework that align environmental, economic, social, and cultural sustainability. In the Indian context—marked by rapid industrialization and growing environmental concerns—a new wave of ecopreneurs has emerged, utilizing business opportunities to promote sustainability. While prior literature emphasized that sustainable practices contribute to environmental preservation, their role in enhancing economic performance (EP), particularly when mediated by innovation, remains underexplored. This study aimed to empirically assess the impact of SMP on EP and to evaluate the moderating role of innovation performance (IP) among Indian small and medium enterprises (SMEs). Methodology : Primary data were collected through a structured questionnaire administered to 350 SME manufacturers across India, using a simple random sampling technique. The relationships between sustainable practices, IP, and EP were analyzed using partial least squares structural equation modeling (PLS-SEM). Findings : The results confirmed that sustainable practices positively impacted EP. Moreover, IP enhanced this relationship, demonstrating its moderating influence. The findings highlighted the synergistic effect of sustainability and innovation in achieving economic success within the Indian SME sector. Practical Implications : This research provided a strategic framework for SME manufacturers to integrate sustainability and innovation into their operations. It addressed the gap in understanding how these dimensions jointly drive economic growth. However, it acknowledged the exclusion of risk-taking behavior—a crucial entrepreneurial trait, especially among Indian women entrepreneurs—as a limitation and suggested its inclusion in future studies. Originality : The study provided empirical evidence bridging sustainability and innovation, offering a novel perspective for Indian manufacturing SMEs.